Rapid evidence assessment protocol for the meta-analysis of initiatives, interventions and programmes that target rural NEETs - Flynn, P.; McCauley, V.; Mujcinovic, A.; Radovic, V.; Bojnec, S.; Simões, F. (Social Sciences, 2022)
The acronym NEET refers to youths aged between 15 and 34 years old who are excluded from employment, education or training. However, historically, the NEET demographic has been depicted as a largely homogenous group. Against this backdrop and given the dependency of rural economies on agricultural practices for survival, such practices have been in decline for a number of years, seriously threatening rural communities’ sustainability. While these rural NEETs can present as registered unemployed and also within the reporting statistics of various different state-funded initiatives, interventions and programmes, in the case of Rural NEETs, there is a dearth of reporting categories that highlight the specificity of this group resulting in their presence being largely overlooked within official dissemination. In order to advance this emergent field of research, presented here is a Rapid Evidence Assessment protocol that will aid future work of the authors and for others to adapt and/or adopt.